Evaluation of the effect of adding probiotic supplementation in patients with chronic spontaneous urticaria - Pelin Kuteyla Can; Utkan Kızıltaç; Kübra Cüre; Ralfi Singer; Ece Nur Degirmentepe; Emek Kocaturk (Dermatologica Sinica)
Background: Altered microbiota has been implicated in the pathogenesis of chronic spontaneous urticaria (CSU). However, studies showing the effects of probiotic supplementation in CSU are scarce. Objectives: The objective of the study was to evaluate the efficacy of oral probiotic supplementation (Lactobacillus reuteri) in patients with CSU. Methods: This was a prospective, nonrandomized, parallel group, and controlled study. Oral probiotic supplementation (L. reuteri ATCC 55730 1 × 108 CFU) and a single dose of ebastine were introduced to 30 CSU patients, whereas a control group of 30 CSU patients received only a single dose of ebastine. Treatment responses, symptom control, and quality of life (QoL) were evaluated with Urticaria Activity Score 7 (UAS7), Physicians’ Global Assessment Visual Analog Score (PhyGA-VAS), and Chronic Urticaria Quality of Life Questionnaire (CU-Q2oL) at weeks 0, 2, and 4. Results: There were significant decreases in the UAS7 and CU-Q2oL and increases in PhyGA-VAS both in the probiotic group and control group at weeks 2 and 4 (P < 0.05; for all). The changes in the UAS7, CU-Q2oL, and PhyGA-VAS were significantly higher in the probiotic group than in the control group (P = 0.026; P = 0.001; and P = 0.004). The number of responders was significantly higher in the probiotic group than in the control group (83.3% vs. 50%, P = 0.006). Complete response and significant clinical improvement were observed in 9 (30%) and 20 (66.7%) patients in the probiotic group and 6 (20%) and 12 (40%) patients in the control group, respectively. High levels of total immunoglobulin E (≥100 IU/mL) were more frequent in probiotic nonresponders than in probiotic responders. Conclusion: Probiotics, when added to the standard therapy may improve the symptoms as well as the QoL scores in the treatment of CSU.